Podosome rings generate forces that drive saltatory osteoclast migration - Dan, Georgess (2011)
Podosomes are dynamic, actin-containing adhesion structures that collectively self-organize as rings. In this study, we first show by observing osteoclasts plated on bead-seeded soft substrates that podosome assemblies, such as rings, are involved in tension forces. During the expansion of a podosome ring, substrate displacement is oriented outward, suggesting that podosomal structures push the substrate away. To further elucidate the function of forces generated by podosomes, we analyze osteoclast migration. Determining the centers of mass of the whole cell (G) and of actin (P), we demonstrate that osteoclasts migrate by “jumps” and that the trajectories of G and P are strongly correlated. The velocity of the center of mass as a function of time reveals that osteoclasts rapidly catch up with podosomal structures in a periodic pattern. We conclude that actin dynamics inside the cell are not only correlated with cell migration, but drive it.